Modeling and numerical simulation of AA1050-O embossed sheet metal stamping. (2017) - Labergere, C.; Badreddine, H.; Msolli, S.; Saanouni, K.; Martiny, M.; Choquart, F.
Abstract: In this paper, a numerical methodology is presented for the stamping simulation of a embossed sheet. A large strains elastoplastic model based on Hill's anisotropic plasticity criteria and coupled with damage is presented and identified in the case of AA1050-O flat sheets. Finally the stamping of an industrial part is simulated and validate the proposed methodology.